1989
DOI: 10.1021/jm00128a010
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarials. 16. Synthesis of 2-substituted analogs of 8-[(4-amino-1-methylbutyl)amino]-6-methoxy-4-methyl-5-[3-(trifluoromethyl)phenoxy]quinoline as candidate antimalarials

Abstract: A series of 2-substituted analogues of the exceptional drug 8-[(4-amino-1-methylbutyl)amino]-6-methoxy-4-methyl-5-[3- (trifluoromethyl)phenoxy]quinoline (I) were prepared and evaluated for both suppressive and prophylactic antimalarial activity. The preparation of analogues of compound I was of interest due to the high level of both blood and tissue schizonticidal activity demonstrated by this compound. One analogue, 8a, was found to be both more active and less toxic than the parent compound I. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 2 publications
0
38
0
1
Order By: Relevance
“…This produced almost 200 PQ derivatives (Tables 2-4) bearing diverse groups in one or more given positions of the ring [6,46,[161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179]. Globally, the most favourable substituent insertions towards anti-malarial activity where those of methyl groups at positions 4 and 2, tert-butyl at position 2, simultaneous insertion of ethyl substituents at positions 2 and 4 and pentyloxy at position 5, as well as insertion at position 5 of alkoxy, fluoro, and 3-or 4-substituted phenoxy groups [51,163].…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 99%
“…This produced almost 200 PQ derivatives (Tables 2-4) bearing diverse groups in one or more given positions of the ring [6,46,[161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179]. Globally, the most favourable substituent insertions towards anti-malarial activity where those of methyl groups at positions 4 and 2, tert-butyl at position 2, simultaneous insertion of ethyl substituents at positions 2 and 4 and pentyloxy at position 5, as well as insertion at position 5 of alkoxy, fluoro, and 3-or 4-substituted phenoxy groups [51,163].…”
Section: Modifications At the Quinoline Ringmentioning
confidence: 99%
“…(4)). Results are given in Table 1 (entries [1][2][3][4][5][6]. The reaction of 2a with diethyl malonate and sodium hydride proceeded smoothly in dry toluene at room temperature, producing 2-substituted malonic acid diethyl ester 4a in high yield (Scheme 1, Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, treatment of 5 and 6a-6d with an excess of polyphophoric acid at 130 8C for a short period gave 2-trifluoromethyl-2,3-dihydroquinolin-4-ones 8 and 9a-9d in fair to good yields (Scheme 4, Eqs. (2) and (3), and Table 4, entries [1][2][3][4][5]. Under the same conditions, treatment of the 4,4,4-trifluoro-3-otolylaminobutyric acid (6e) gave only a small amount of the 2,3-dihydroquinolin-4-one 9e (entry 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that introducing an alkyl or alkoxy group at position 2 of the aromatic ring reduces the toxicity of a compound (induction of methemoglobin). 20,21 Scheme 1 describes the synthesis of compound 1. Compounds 2-6 were synthesized in similar routes.…”
mentioning
confidence: 99%